Influence of elevated temperature on physical properties and compressive strength of concrete containing laterite as partial fine aggregate replacement - Fatin Ajeerah, Mad Din (2015)
Negative impact of sand mining includes erosion, loss of biodiversity, and soil contamination by chemicals from mining processes also one reason why laterite is being used as replacement. The impact of temperature rise on mass loss, compressive strength, and physical appearance on performance of concrete containing various percentage of laterite replacement has been investigated. Depletion of fine sand aggregate has led to production of concrete containing laterite as partial fine aggregate replacement. Laterite concrete can be used for structures such as buildings and also special structures for special purposes. The behaviour of laterite concrete upon fire outbreak is important to be known. In this study, the physical properties and compressive strength of concrete containing laterite aggregate as partial fine aggregate replacement has been carried out. Two types of mix have been used in this experimental work that is plain concrete (control specimen) and laterite concrete of various percentage of laterite aggregate. All the specimen were water cured for 28 day before testing. The specimens were exposed to a range of temperature beginning from 28°C until 800°C. Water cooling method was used to cool down the specimen after exposed to subjected temperature. It was found that the mass loss and compressive strength of the concrete decreased as the temperature increase. From the results, the strength of laterite concrete with 20% replacement of fine aggregate is better than plain concrete.